Method for preparing type II anhydrite and activating activity of type II anhydrite
By adding composite converter and surfactant to the gypsum and using calcium active materials and sulfate excitants for active activation, the problems of high energy consumption and complex process in the production of type II anhydrous gypsum are solved, and a low-cost, low-energy consumption preparation process and high-performance products are realized.
Patent Information
- Application Number
- CN202411730603.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing Type II anhydrous gypsum production methods have problems such as high energy consumption, complex process, low production capacity and secondary pollution, making it difficult to achieve large-scale production and market competitive advantages.
By adding a composite conversion agent and surfactant to the gypsum, the activation energy and surface tension of the gypsum are reduced, the conversion of dihydrate gypsum to type II anhydrous gypsum is promoted, and the active activation is used for calcified active materials and sulfate excitants are adjusted to adjust the initial settling time and strength of the product.
It realizes the preparation of type II anhydrous gypsum with low cost and low energy consumption, simplifies the process flow, improves production efficiency and the physical and mechanical properties of the products, and expands application scenarios.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of comprehensive utilization of solid waste building materials, and specifically relates to a method for preparing type II anhydrous gypsum and activating its activity. Background Art
[0002] Gypsum can be divided into natural gypsum and chemical gypsum. Chemical gypsum refers to slag or by-product with calcium sulfate as the main component produced in the chemical industry or other industrial production processes, such as phosphogypsum, sulfur gypsum, water treatment gypsum and other gypsum produced in the form of dihydrate. Gypsum obtained from different origins and different processes is quite different. For example, the gypsum content and impurities of natural gypsum vary significantly depending on its origin. In addition to calcium sulfate, phosphogypsum also contains incompletely decomposed phosphate rock, residual phosphoric acid, fluoride, acid insoluble matter, organic matter, etc. Among them, fluorine can endanger human health, mainly manifested as yellowing of teeth and bone deformation. After phosphorus enters the soil, it will cause soil compaction and alkalization. When it enters the water body, it will cause eutrophication of the water body, leading to rapid reproduction of algae and lack of oxygen in the water, causing fish deaths, etc. Therefore, the presence of fluorine and phosphorus directly affects their resource utilization. Desulfurization gypsum is a by-product of tail gas desulfurization in coal-fired boilers and metallurgical industries. In addition to the main component of calcium sulfate dihydrate, it also contains impurities such as fly ash, organic carbon, calcium carbonate, calcium sulfite and various soluble salts. The color can be white, gray or yellow, depending on the conditions during the desulfurization process. These components have a certain impact on the performance of gypsum products.
[0003] Gypsum is mainly used in the building materials industry, such as cement retarder and production of building gypsum. There is a large space for the development of building gypsum. At present, the proportion of gypsum building materials in my country is less than 20%, far lower than the 80% in developed countries. On the one hand, it is affected by the traditional customs of blue bricks and blue tiles, and on the other hand, it is restricted by the low softening coefficient of gypsum building materials and cannot be used as exterior walls. So far, the main products of gypsum building materials processing are β powder, i.e. building gypsum powder, α high-strength gypsum and anhydrous type II gypsum. Among these three types of products, the production cost of building gypsum is low, but its physical and mechanical properties are poor; α high-strength gypsum has superior physical and mechanical properties, but its production cost is high, and due to the complex process, it is generally produced intermittently with a small processing volume; the physical and mechanical properties of anhydrous type II gypsum are between building gypsum and α high-strength gypsum, and it can be produced on a large scale, but its energy consumption is high, resulting in high production costs and no market competitive advantage. Therefore, developing a low-cost anhydrous type II gypsum production technology and solving the problem of low softening coefficient of gypsum products at the same time is expected to replace cement-based products in many building materials products. At the same time, utilizing its easy molding and adjustable initial and final setting characteristics, it will surely become a leading product in the field of prefabricated buildings.
[0004] So far, there are two main processes for the treatment and utilization of anhydrous type II gypsum, namely calcination and hydrothermal method. In the calcination method, the crystal water of dihydrate gypsum is usually evaporated quickly through the crystal surface at a temperature of 400-800℃, without changing the microscopic morphology of the original dihydrate gypsum. The microscopic morphology of the anhydrous gypsum obtained is usually rhombus-shaped. In the hydrothermal method, the dihydrate gypsum is first dissolved to release Ca2+ under the action of compound conversion agents and other additives. 2+ With SO4 2- When the concentration of these ions reaches the supersaturation of anhydrous gypsum, anhydrous gypsum crystal nuclei will be formed. As the dihydrate gypsum continues to dissolve, the anhydrous gypsum crystals gradually grow, which is the process of dissolution-recrystallization. The microscopic morphology of the anhydrous gypsum produced is different from the crystal morphology of the original dihydrate gypsum, and is usually in the form of flakes, needles or long fibers.
[0005] Chinese invention patent ZL202110646751.0 discloses a device and method for producing type II anhydrous gypsum using industrial by-product gypsum. The device includes a feeding unit, a drying unit, a calcination unit, a crystal control unit and a product collection unit connected in sequence; the calcination unit can effectively remove the crystal water in the dihydrate gypsum to obtain a crude type II anhydrous gypsum, and then the temperature and residence time are controlled by the crystal type controller to achieve precise step-by-step crystal control to obtain a type II anhydrous gypsum product with an AⅡ-U crystal type proportion of ≥98wt%.
[0006] Chinese invention patent ZL202010181986.2 discloses a type II anhydrous gypsum roasting process, comprising the following steps: (1) preparing a phosphogypsum raw material containing 10% water; (2) feeding the phosphogypsum raw material into a de-impurity screen to remove large particles of impurities; (3) feeding the phosphogypsum raw material with large particles of impurities removed into a flash dryer, and using two-way convection hot air for convection drying to remove attached water; (4) using a cyclone dust collector and a bag dust collector to collect the phosphogypsum raw material from which attached water has been removed, and feeding it into an internal heat pipe rotary roasting kiln through a lifting and conveying device; (5) in the internal heat pipe rotary roasting kiln, the phosphogypsum is peristalticized and stir-fried through the internal heat pipe to generate secondary steam of the crystal water in the phosphogypsum, and adjusting the rotation speed of the internal heat pipe rotary roasting kiln so that the temperature of the phosphogypsum raw material rises to 420°C-480°C to obtain slowly soluble anhydrous gypsum.
[0007] Chinese invention patent ZL202210206416.3 discloses a system for producing high-purity gypsum using industrial by-product gypsum, characterized in that the system includes a pretreatment subsystem, a calcination subsystem, a cooling subsystem and a flue gas treatment subsystem.
[0008] Chinese invention patent ZL202410662144.7 discloses a method for preparing type II anhydrous gypsum: mixing sulfuric acid with a mass concentration of 30-80% and an acid etching agent accounting for 0-5% of the weight of the sulfuric acid to obtain a mixed acid, adding industrial gypsum to the mixed acid for dehydration reaction, filtering, washing and drying the dehydrated product. The entire process of the present invention does not require the "dissolution-recrystallization" process, has a short processing time, high efficiency, simple process, mild conditions, energy saving and emission reduction, and the obtained type II anhydrous gypsum product has high purity and low impurities.
[0009] Chinese invention patent ZL202211624297.X discloses a method for preparing type II anhydrous gypsum from high silicon phosphogypsum, which relates to the technical field of phosphogypsum processing. 2 O 5 The wet phosphoric acid solution is added with hydrofluoric acid to obtain a mixed solution; phosphogypsum is added to the mixed solution, and sulfuric acid solution is added dropwise, the reaction temperature is controlled to be 90-100°C, and the reaction is stirred for 4-8 hours; the reaction slurry is filtered, washed, and dried to obtain type II anhydrous gypsum. By using a mixed acid system of wet phosphoric acid, hydrofluoric acid, and sulfuric acid, phosphogypsum is recrystallized at a certain temperature to obtain type II anhydrous gypsum. In the process, hydrofluoric acid reacts with silicon dioxide to obtain fluorosilicic acid, which adsorbs calcium ions and promotes the formation of large-particle crystals of anhydrous gypsum, which is conducive to filtering and washing, removing impurities such as organic matter, and further improving the quality of anhydrous gypsum. It not only realizes the transformation of phosphogypsum into anhydrous gypsum, but also purifies the quality of anhydrous gypsum.
[0010] In summary, the current production methods of type II anhydrous gypsum are all concentrated on calcination and liquid phase methods. The main reason for the lack of large-scale application is that the calcination method has high energy consumption, the liquid phase method has complex process, long crystallization time, and harsh washing conditions. Compared with phosphogypsum, the treated liquid can be used as the main production coefficient for recycling, but other gypsums do not have the conditions for promotion. Therefore, the present invention intends to add a composite conversion agent to achieve directional crystallization while reducing the dehydration activity of gypsum, thereby solving the problems of high energy consumption of the traditional type II anhydrous gypsum calcination method, low production capacity of the liquid phase method, and secondary pollution. Summary of the invention
[0011] The purpose of the present invention is to provide a method for preparing a type II anhydrous gypsum product by utilizing an active excitation method to solve the problems of high energy consumption and difficulty in large-scale production in the prior art.
[0012] To achieve the above-mentioned purpose, the technical scheme of the present invention is to provide a method for preparing type II anhydrous gypsum and stimulating its activity. One of the innovative points is that a composite conversion agent is added to the gypsum to reduce the dehydration activation energy of dihydrate gypsum, and a surfactant is added at the same time to reduce the surface tension of the gypsum, increase the contact and infiltration of the composite conversion agent with the gypsum, and promote the conversion of dihydrate gypsum to type II anhydrous gypsum; the second innovative point is that type II anhydrous gypsum has low activity and needs to add an activator to dissolve and recrystallize it. Since the type II anhydrous gypsum prepared by the present invention contains a small amount of free acid, the traditional sulfate excitation will cause the final product to be highly acidic, which limits its application environment. Therefore, the present invention adopts a calcium active material as a main activator and cooperates with a sulfate activator to neutralize its acidity while obtaining a hydraulic component, thereby improving the strength of the product while increasing its softening coefficient, and expanding the product application path.
[0013] The specific contents of the present invention are as follows:
[0014] A method for preparing type II anhydrous gypsum, characterized in that it comprises the following steps:
[0015] S1, mixing: adding a composite conversion agent and a surfactant to gypsum and mixing evenly to obtain a mixture;
[0016] The compound conversion agent is a mixture of pure strong acid, citric acid and aluminum sulfate, and the dosage thereof is 1-3%, 0.5-1.0% and 0-0.5% of the dry mass of gypsum respectively;
[0017] The dosage of the surfactant is 0.03-0.05% of the dry mass of gypsum;
[0018] S2, phase conversion: hot air at a temperature of 120-200° C. is introduced into the mixture obtained in step S1 for heating and dehydration for 20-60 min to obtain type II anhydrous gypsum.
[0019] The gypsum in step S1 can be natural gypsum or chemical gypsum, wherein the attached water content is 10-20% or water is added to adjust to the corresponding water content. The chemical gypsum is phosphogypsum or desulfurized gypsum.
[0020] The purified strong acid described in step S1 is one of sulfuric acid, hydrochloric acid and nitric acid.
[0021] The surfactant described in step S1 is one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide and polyethylene glycol.
[0022] In step S2, heating and dehydration are carried out in a rotary kiln.
[0023] The present invention also discloses a method for activating the obtained type II anhydrous gypsum, which is characterized by comprising the following steps:
[0024] s1. Mechanical activation: Grind the type II anhydrous gypsum to a specific surface area of 400±20m 2 / kg, that is, mechanical activation is completed;
[0025] s2. Add active calcium activator, salt activator and modifier to the type II anhydrous gypsum after mechanical activation in step s1, and mix them evenly to obtain the type II anhydrous gypsum product; the active calcium activator is quicklime and cement clinker, and the amount thereof is 10-18% and 2-10% of the mass of the type II anhydrous gypsum, respectively;
[0026] The salt activator is a sulfate, and its dosage is 0.5-1.0% of the mass of type II anhydrous gypsum;
[0027] The dosage of the modifier is 0.05-0.1% of the mass of type II anhydrous gypsum.
[0028] The sulfate described in step s2 is sodium sulfate or alunite.
[0029] The modifier described in step s2 is one of calcium lignin sulfonate and sodium lignin sulfonate.
[0030] The type II anhydrous gypsum product obtained in step s2 has a standard consistency water consumption of 40-45%, an initial setting time of 30-60 min, a final setting time of 120-180 min, a 28-day flexural strength of >6 MPa, a softening coefficient of >0.8, and a compressive strength of >25 MPa.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) Compared with the existing mature calcination method, the method of the present invention has a low conversion temperature and low cost. Compared with the liquid phase method, the production process is simple, the production capacity is large, the conversion time is short, and there is no wastewater disposal problem. In summary, the present invention has a good prospect for promotion and application.
[0033] (2) The dehydration conversion process of the method of the present invention is similar to that of β-building gypsum, but the present invention is less sensitive to temperature and has a wide temperature operating range. The dehydration conversion process can be directly heated, with fast heat transfer. The heat utilization rate is higher than that of the β-building gypsum production method, and the production capacity is large.
[0034] (3) The active activation of type II anhydrous gypsum prepared by the method of the present invention is mainly based on calcium active materials. Under the synergistic effect of salt activator and surface modifier, the initial and final setting time can be adjusted. The solidification product of the solidified body has both air-hardening and water-hardening characteristics. The 28-day flexural strength is >6MPa, the compressive strength is >25MPa, and the softening coefficient is >0.8. Compared with cement-based materials, it is more energy-saving and environmentally friendly and is a low-carbon product. Compared with traditional gypsum products, it has a high softening coefficient, breaking the limitation that traditional gypsum cannot be used as exterior wall materials, and has a wider application scenario. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a process flow chart of the present invention;
[0036] Figure 2 XRD spectra of raw materials and heat-treated materials in Example 1 of the present invention;
[0037] Figure 3 These are SEM images of the specimens of Example 1 of the present invention at different ages. DETAILED DESCRIPTION
[0038] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited by the embodiments.
[0039] Example 1
[0040] The raw material of this embodiment is phosphogypsum, and its main composition is shown in Table 1:
[0041] Table 1 Main chemical composition of phosphogypsum raw materials (wt%)
[0042] name CaO <![CDATA[SO 3 ]]> <![CDATA[SiO 2 ]]> MgO <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[P 2 THE 5 ]]> F Crystal water <![CDATA[CaSO 4 .H2O]]> Adherent water content 29.71 41.99 5.67 0.65 0.50 0.47 1.77 0.13 18.78 90.38 20
[0043] In parts by mass, 100 parts of the above-mentioned phosphogypsum raw material dry basis are taken, 3 parts of pure hydrochloric acid, 1.0 parts of citric acid, and 0.05 parts of sodium dodecylbenzene sulfonate are added, and then mixed thoroughly, and then sent to a rotary kiln through a belt conveyor, and hot air at a temperature of 120°C is introduced and left for 60 minutes to obtain type II anhydrous gypsum. Theoretically, the content of type II anhydrous gypsum formed after the phosphogypsum is completely dehydrated and converted is 88.16%. The XRD spectra of the raw materials in this embodiment and the type II anhydrous gypsum obtained after heat treatment are as follows: Figure 2 shown.
[0044] Grind this type II anhydrous gypsum to a specific surface area of 380m 2 / kg, the phase composition of type II anhydrous gypsum obtained by analysis is shown in Table 2 below:
[0045] Table 2 Phase composition analysis of type II anhydrous gypsum in Example 1
[0046] composition AⅢ HH DH AⅡ Adherent water Content (wt%) 4.23 2.80 0.85 79.60 0.5
[0047] According to calculation, the conversion rate of type II anhydrous gypsum in this case is 90.3%.
[0048] For every 100 parts of ground type II anhydrous gypsum, add active calcium activator including 10 parts of quicklime and cement clinker, 1.0 part of alum stone and 0.1 part of calcium lignin sulfonate, and mix well to obtain type II anhydrous gypsum product.
[0049] After testing, the product has a standard consistency of water consumption of 40%, an initial setting time of 30 minutes, a final setting time of 120 minutes, a 28-day flexural strength of 7.55 MPa, and a compressive strength of 30.72 MPa. The softening coefficient is 0.89. The SEM images of the specimens of this embodiment at different ages are as follows: Figure 3 shown.
[0050] Example 2
[0051] The raw material of this case is natural gypsum, and its main composition is shown in Table 3:
[0052] Table 3 Main chemical components of natural gypsum raw materials (wt%)
[0053] name CaO <![CDATA[SO 3 ]]> <![CDATA[SiO 2 ]]> MgO <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[P 2 THE 5 ]]> F Crystal water <![CDATA[CaSO 4 .H2O]]> Adherent water content 31.14 44.56 2.67 0.34 0.20 0.12 0.05 0.01 20.03 95.42 6.8
[0054] The above natural gypsum powder is added with water to adjust the attached water content to 10%. By mass, 100 parts of the above natural gypsum dry basis are taken, 3 parts of pure sulfuric acid, 0.5 parts of citric acid, 0.5 parts of aluminum sulfate, and 0.03 parts of hexadecyltrimethylammonium bromide are added, and then mixed evenly. Then, the mixture is sent to a rotary kiln through a belt conveyor, and hot air at a temperature of 200°C is introduced and left for 30 minutes to obtain type II anhydrous gypsum. Theoretically, the content of type II anhydrous gypsum formed after the natural gypsum is completely dehydrated and converted is 94.39%. This type II anhydrous gypsum powder is ground to a specific surface area of 420m 2 / kg, the phase composition of type II anhydrous gypsum obtained by analysis is shown in Table 4 below:
[0055] Table 4 Phase composition analysis of type II anhydrous gypsum in Example 2
[0056] composition AⅢ HH DH AⅡ Adherent water Content (wt%) 1.23 2.42 1.05 89.86 0.0
[0057] According to calculation, the conversion rate of type II anhydrous gypsum in this case is 95.2%.
[0058] For every 100 parts of ground type II anhydrous gypsum, add active calcium activator, including 18 parts of quicklime and 2 parts of cement clinker, 0.5 part of sodium sulfate, and 0.05 part of calcium lignin sulfonate. After mixing evenly, the type II anhydrous gypsum product is obtained.
[0059] According to the test, the water consumption of the product at standard consistency is 45%, the initial setting time is 60 minutes, the final setting time is 180 minutes, the 28-day flexural strength is 6.20 MPa, the compressive strength is 26.72 MPa, and the softening coefficient is 0.82.
[0060] Example 3
[0061] Taking desulfurized gypsum as raw material, its main composition is shown in Table 5:
[0062] Table 5 Main chemical composition of desulfurized gypsum raw materials (wt%)
[0063] name CaO <![CDATA[SO 3 ]]> <![CDATA[SiO 2 ]]> MgO <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[P 2 THE 5 ]]> F Crystal water <![CDATA[CaSO 4 .H2O]]> Adherent water content 27.73 39.72 7.87 3.65 1.65 0.78 0.12 0.01 17.81 85.26 15
[0064] In terms of mass, 100 parts of the above desulfurized gypsum raw material are taken, 3 parts of pure nitric acid, 0.7 parts of citric acid, 0.3 parts of aluminum sulfate, sodium dodecylbenzene sulfonate and polyethylene glycol are added as surfactants, the amount of each of which accounts for 50%, and the total amount is 0.04% of the dry mass of chemical gypsum. After being fully mixed, it is sent to a rotary kiln through a belt conveyor, and hot air at a temperature of 170°C is introduced and left for 40 minutes to obtain type II anhydrous gypsum. Theoretically, the content of type II anhydrous gypsum formed after the desulfurized gypsum is completely dehydrated and converted is 82.03%. This type II anhydrous gypsum is ground to a specific surface area of 400m 2 / kg, the phase composition of type II anhydrous gypsum obtained by analysis is shown in Table 6 below:
[0065] Table 6 Phase composition analysis of type II anhydrous gypsum in Example 3
[0066] composition AⅢ HH DH AⅡ Adherent water Content (wt%) 3.46 1.40 1.35 75.87 0.2
[0067] According to calculation, the conversion rate of type II anhydrous gypsum in this case is 92.5%.
[0068] For every 100 parts of ground type II anhydrous gypsum, add active calcium activator including 15 parts of quicklime, 5 parts of cement clinker, 0.5 parts of sodium sulfate, 1.0 parts of alum stone and 0.1 parts of calcium lignin sulfonate, and mix well to obtain type II anhydrous gypsum product.
[0069] According to the test, the water consumption of the product at standard consistency is 45%, the initial setting time is 45 minutes, the final setting time is 123 minutes, the 28-day flexural strength is 5.85 MPa, the compressive strength is 25.92 MPa, and the softening coefficient is 0.85.
Claims
1. A method for preparing type II anhydrous gypsum, characterized in that: The following steps are involved: S1, mixing: adding a composite conversion agent and a surfactant to gypsum and mixing evenly to obtain a mixture; The compound conversion agent is a mixture of pure strong acid, citric acid and aluminum sulfate, and the dosage thereof is 1-3%, 0.5-1.0% and 0-0.5% of the dry mass of gypsum respectively; The dosage of the surfactant is 0.03-0.05% of the dry mass of gypsum; S2, phase conversion: hot air at a temperature of 120-200° C. is introduced into the mixture obtained in step S1 for heating and dehydration for 20-60 min to obtain type II anhydrous gypsum.
2. The method for preparing type II anhydrous gypsum according to claim 1, characterized in that: The gypsum in step S1 can be natural gypsum or chemical gypsum, wherein the attached water content is 10-20% or water is added to adjust to the corresponding water content.
3. The method for preparing type II anhydrous gypsum according to claim 2, characterized in that: The chemical gypsum is phosphogypsum or desulfurized gypsum.
4. The method for preparing type II anhydrous gypsum according to claim 1, characterized in that: The purified strong acid described in step S1 is one of sulfuric acid, hydrochloric acid and nitric acid.
5. The method for preparing type II anhydrous gypsum according to claim 1, characterized in that: The surfactant described in step S1 is one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide and polyethylene glycol.
6. The method for preparing type II anhydrous gypsum according to claim 1, characterized in that: It is characterized in that In step S2, the heating and dehydration is carried out in a rotary kiln.
7. A method for activating the type II anhydrous gypsum obtained in any one of claims 1 to 6, characterized in that: The following steps are included: s1. Mechanical activation: Grind the type II anhydrous gypsum to a specific surface area of 400±20m 2 / kg, that is, mechanical activation is completed; s2, adding active calcium activator, salt activator and modifier to the type II anhydrous gypsum after mechanical activation in step s1, and mixing them evenly to obtain the type II anhydrous gypsum product; The active calcium activator is quicklime and cement clinker, and the dosage thereof is 10-18% and 2-10% of the mass of type II anhydrous gypsum respectively; The salt activator is a sulfate, and its dosage is 0.5-1.0% of the mass of type II anhydrous gypsum; The dosage of the modifier is 0.05-0.1% of the mass of type II anhydrous gypsum.
8. A method for activating the activity of type II anhydrous gypsum according to claim 7, characterized in that: The sulfate described in step s2 is sodium sulfate or alunite.
9. A method for activating the activity of type II anhydrous gypsum according to claim 7, characterized in that: The modifier described in step s2 is one of calcium lignin sulfonate and sodium lignin sulfonate.
10. A method for activating the activity of type II anhydrous gypsum according to claim 7, characterized in that: The type II anhydrous gypsum product obtained in step s2 has a standard consistency water consumption of 40-45%, an initial setting time of 30-60 min, a final setting time of 120-180 min, a 28-day flexural strength of >6 MPa, a softening coefficient of >0.8, and a compressive strength of >25 MPa.
Citation Information
Patent Citations
Method for utilizing solid waste ardealite to prepare gypsum whiskers
CN105088347A
Method for preparing high-strength anhydrous gypsum from sulfur-calcium slag
CN110981242A
Method for preparing self-leveling mortar from phosphorus type II anhydrite
CN116621555A
Manufacturing method for ii-gypsum anhydrite
KR100710483B1